Ice‐Marginal Proglacial Lakes Across Greenland: Present Status and a Possible Future - Jonathan L. Carrivick; Penelope How; James M. Lea; Jenna L. Sutherland; Michael Grimes; Fiona S. Tweed; Stephen Cornford; Duncan J. Quincey; Joseph Mallalieu (Geophysical Research Letters)
Abstract Ice‐marginal lakes can affect glacier dynamics but are ignored in studies of the evolution of the Greenland ice sheet (GrIS) and of peripheral mountain glaciers and ice caps (PGICs). Here we show that lakes occupy 10% of the GrIS ice margin and occur on 5% of PGICs. Ice velocity at the GrIS margin is enhanced by ∼ 25% at lakes versus on land. Mean ice discharge into lakes is ∼4.9 Gt.yr, which is ∼1% of ice discharged through marine termini. We locate thousands of subglacial overdeepenings within which 7,404 km2 of future lakes could form, all of which will be ice‐marginal at some time. Future lakes in the west and east will be restricted to the margin of the GrIS and within alpine valleys, respectively. This status and possible future leads us to contend that lakes should be incorporated into projections of Greenland ice loss.